A High-Throughput Interbacterial Competition Screen Identifies ClpAP in Enhancing Recipient Susceptibility to Type VI Secretion System-Mediated Attack by Agrobacterium tumefaciens - Lin, Hsiao-Han; Yu, Manda; Sriramoju, Manoj Kumar; Hsu, Shang-Te Danny; Liu, Chi-Te; Lai, Erh-Min (Frontiers in Microbiology, 2020)
The type VI secretion system (T6SS) is an effector delivery system used by Gram-negative bacteria to kill other bacteria or eukaryotic hosts to gain fitness. The plant pathogen Agrobacterium tumefaciens utilizes its T6SS to kill other bacteria, such as Escherichia coli. We observed that the A. tumefaciens T6SS-dependent killing outcome differs when using different T6SS-lacking, K-12 E. coli strains as a recipient cell. Thus, we hypothesized that the A. tumefaciens T6SS killing outcome not only relies on the T6SS activity of the attacker cells but also depends on the recipient cells. Here, we developed a high-throughput interbacterial competition platform to test the hypothesis by screening for mutants with reduced killing outcomes caused by A. tumefaciens strain C58. Among the 3909 strains in the E. coli Keio library screened, 16 mutants with less susceptibility to A. tumefaciens C58 T6SS-dependent killing were identified, and four of them were validated by complementation test. Among the four, the clpP encoding ClpP protease that is universal and highly conserved in both prokaryotes and eukaryotic organelles was selected for further characterizations. We demonstrated that ClpP is responsible for enhancing susceptibility to the T6SS killing. Because ClpP protease depends on other adapter proteins such as ClpA and ClpX for substrate recognition, further mutant studies followed by complementation tests were carried out to reveal that ClpP-associated AAA+ ATPase ClpA, but not ClpX, is involved in enhancing susceptibility to A. tumefaciens T6SS killing. Moreover, functional and biochemical studies of various ClpP amino acid substitution variants provided evidence that ClpA-ClpP interaction is critical in enhancing susceptibility to the T6SS killing. This study highlights the importance of recipient factors in determining the outcome of the T6SS killing and shows the universal ClpP protease as a novel recipient factor hijacked by the T6SS of A. tumefaciens.